Intergenerational Wealth Mobility in England, 1858–2012: Surnames and Social Mobility. (19th September 2014) - Clark, Gregory; Cummins, Neil
<x xml:space="preserve">Abstract</x> This article uses a panel of 18, 869 people with rare surnames whose wealth is observed at death in England and Wales 1858–2012 to measure the intergenerational elasticity of wealth over five generations. We show, using rare surnames to track families, that wealth is much more persistent than standard one generation estimates would suggest. There is still a significant correlation between the wealth of families five generations apart. We show that this finding can be reconciled with standard estimates of wealth mobility by positing an underlying first order Markov process of wealth inheritance with an intergenerational elasticity of 0.70–0.75 throughout the years 1858–2012.